Pengaruh Good Corporate Governance Terhadap Tax Avoidance Dengan Moderasi Gender Diversity - Laurensia, Cindy; Haryono, Haryono; Mustika, Ira Grania (JCA (Jurnal Cendekia Akuntansi), 2024)
A quantitative approach was adopted in this study to examine the influence of good corporate governance on tax avoidance in consumer cyclicals companies listed on the Indonesia Stock Exchange during 2021-2023 with gender diversity as moderation. Through purposive sampling, 44 companies that met the criteria were selected for a three-year observation period, resulting in 132 data observations. The analysis method used in this study are multiple linear regression analysis and moderated regression analysis by using SPSS 25. The findings of this study indicate that good corporate governance, proxied by the size of board of directors, independent commissioners, and audit committees, does not have a significant impact on tax avoidance, while executive compensation shows a significant positive influence on tax avoidance. Meanwhile, gender diversity was not able to moderate the influence of good corporate governance on tax avoidance.